Dinamika Transportasi Berbasi Online Di Era Revolusi Industri 4.0 - Ramlah Puji Astuti; Siti Kumayah; Agustina Agustina (FEB Universitas Sultan Ageng Tirtayasa, 2020)
Industry challenges and opportunities 4.0 encourage innovation and creation from all walks of life, one of is the growth of Online Based Transportation (TBO). The purpose of this research is to more closely observe and examine the extent of the role and impact of Online Based Transportation in the Industrial Revolution Era 4.0 for the economic development of society in Cirebon. This research method uses a combination of research methods (Mixed Methods). The results of this study indicate that there is a positive influence on car drivers, motorcycle driver partners and merchants in the city of Cirebon. Based on a survey and analysis of the results of the discussion of the existence of online transportation is very influential (impact) on the socio-economic community in the city of Cirebon. The survey results show that 78% of respondents said online transportation had a good (positive) impact. Hypothesis testing show that the existence of online transportation has a significant effect on the socio-economic community in Cirebon.